An introduction to education research methods: exploring the learning journey of pre-service teachers in a transnational programme. Issue 1 (1st January 2016) - White, Sonia; Hepple, Erika; Tangen, Donna; Comelli, Marlana; Alwi, Amyzar; Abu Hassan Shaari, Zaira
Abstract : Internationally there is interest in developing the research skills of pre-service teachers as a means of ongoing professional renewal with a distinct need for systematic and longitudinal investigation of student learning. The current study takes a unique perspective by exploring the research learning journey of pre-service teachers participating in a transnational degree programme. Using a case-study design that includes both a self-reported and direct measure of research knowledge, the results indicate a progression in learning, as well as evidence that this research knowledge is continued or maintained when the pre-service teachers return to their home university. The findings of this study have implications for both pre-service teacher research training and transnational programmes.